2011
DOI: 10.1101/cshperspect.a006916
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Posttranscriptional Regulation of HIV-1 Gene Expression

Abstract: Control of HIV-1 gene expression depends on two viral regulatory proteins, Tat and Rev. Tat stimulates transcription elongation by directing the cellular transcriptional elongation factor P-TEFb to nascent RNA polymerases. Rev is required for the transport from the nucleus to the cytoplasm of the unspliced and incompletely spliced mRNAs that encode the structural proteins of the virus. Molecular studies of both proteins have revealed how they interact with the cellular machinery to control transcription from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
383
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(389 citation statements)
references
References 137 publications
4
383
0
2
Order By: Relevance
“…As discussed in other articles in this collection (Hu and Hughes 2011;Karn and Stoltzfus 2011;Malim and Bieniasz 2011), the relative contribution of these mechanisms is a matter of some debate. Whatever the source, the overall single-step point mutation rate for HIV-1 is 3 Â 10 25 mutations per base per replication cycle, and about 10-fold less for transversions than transitions (Mansky and Temin 1995).…”
Section: Mutationmentioning
confidence: 99%
“…As discussed in other articles in this collection (Hu and Hughes 2011;Karn and Stoltzfus 2011;Malim and Bieniasz 2011), the relative contribution of these mechanisms is a matter of some debate. Whatever the source, the overall single-step point mutation rate for HIV-1 is 3 Â 10 25 mutations per base per replication cycle, and about 10-fold less for transversions than transitions (Mansky and Temin 1995).…”
Section: Mutationmentioning
confidence: 99%
“…Splicing has to be strictly regulated to allow the balanced production of all viral RNAs and proteins. The HIV-1 transcript contains several SREs to enhance or inhibit splicing at nearby positioned splice sites (Damgaard et al, 2002;Karn & Stoltzfus, 2012;Leblanc et al, 2013;Stoltzfus, 2009;Stoltzfus & Madsen, 2006;Tange et al, 2001;Zahler et al, 2004). Furthermore, usage of HIV-1 splice sites can be influenced by local RNA structure (Abbink & Berkhout, 2008;Jacquenet et al, 2001;Mueller et al, 2014;Zychlinski et al, 2009 59 ), which will allow efficient U1 snRNA annealing and splicing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that various factors operating at the levels of transcription and posttranscription can restrict the expression of the integrated provirus in resting CD4 ϩ T cells (5,6). Transcriptional blocks to productive HIV-1 replication include epigenetic modifications at the viral long terminal repeat (LTR) and inadequate availability of activation-dependent transcription factors such as P-TEFb, NF-B, NFAT, Sp1, AP-1, and C/EBP (7)(8)(9)(10).…”
mentioning
confidence: 99%